Age-related changes of malondialdehyde, body weight and organ weight in male mice - Ahsani, Dwi Nur; Fidianingsih, Ika (Universa Medicina, 2018)
IntroductionAging is characterized by gradual impairment in all physiological functions. Increases in free radicals and changes in organ morphology occur with aging. The purpose of this study was to determine age-related changes in serum free radicals, body weight, organ weights, and relative organ weights in male mice. MethodsAn experimental animal study was performed on 25 male mice (Mus musculus), which were randomized into 5 groups according to age at termination, i.e. 12 (group K1), 24 (K2), 32 (K3), 40 (K4) and 48 weeks (K5), respectively. Retro-orbital venous blood was taken for examination of malondialdehyde (MDA) levels. After termination, liver, heart, kidneys, testes, brain, thymus and spleen were weighed using an analytical balance. ANOVA and Kruskal Wallis tests were used to analyze the data, with p<0.05 being considered significant. ResultsSignificant changes were found with age in serum MDA level (p=0.000), body weight (p=0.000), and weights of all organs except thymus (p>0.05) (liver p=0.023, heart p=0.000, kidneys p=0.002, testes p=0.000, brain p=0.012 and spleen p=0.006). Significant changes in relative weight of brain (p=0.001) and spleen (p=0.049) were also found with age. ConclusionThis study demonstrated increases in serum MDA levels, body weight, and weights of the liver, heart, kidneys, testes, brain and spleen with age. Peak increases in weights of kidneys and thymus were found earlier than those in MDA levels and weights of other organs.